2021
DOI: 10.1016/j.lanepe.2021.100188
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on incidence, time of diagnosis and delivery of healthcare among paediatric oncology patients in Germany in 2020: Evidence from the German Childhood Cancer Registry and a qualitative survey

Abstract: Background The indirect impact of the COVID-19 pandemic on cancer care and timely diagnosis is of increasing concern. We investigated the impact of the COVID-19 pandemic on incidence, time of diagnosis and delivery of healthcare among paediatric oncology patients in Germany in 2020. Methods We analysed incident paediatric cancer cases diagnosed in 0- to 17-year olds in Germany in 2020 using data of the German Childhood Cancer Registry. Absolute numbers and age-standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 24 publications
2
26
1
4
Order By: Relevance
“…These findings were corroborated in a third study from Belgium, as there was a 44% reduction in the diagnoses of invasive cancers in this country in April 2020 compared with April 2019 (Peacock et al 2021 ). Similar results emerged from the majority of studies conducted in Germany at the early stage of the COVID-19 pandemic (Erdmann et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Stang et al 2020 ; Voigtländer et al 2021 ). A study from Saxony revealed that the number of new cases of cancer decreased in this state between January and September 2020 compared with the same period in 2017–2019 (Piontek et al 2021 ), while another study, using data collected in North Rhine-Westphalia, reported a decrease in new cancer cases in January–September 2020 compared with 2019 (Stang et al 2020 ).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…These findings were corroborated in a third study from Belgium, as there was a 44% reduction in the diagnoses of invasive cancers in this country in April 2020 compared with April 2019 (Peacock et al 2021 ). Similar results emerged from the majority of studies conducted in Germany at the early stage of the COVID-19 pandemic (Erdmann et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Stang et al 2020 ; Voigtländer et al 2021 ). A study from Saxony revealed that the number of new cases of cancer decreased in this state between January and September 2020 compared with the same period in 2017–2019 (Piontek et al 2021 ), while another study, using data collected in North Rhine-Westphalia, reported a decrease in new cancer cases in January–September 2020 compared with 2019 (Stang et al 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…In the past months, a substantial body of literature has investigated the effects of the COVID-19 crisis on cancer diagnosis (Andrew et al 2021 ; De Luca et al 2021 ; Erdmann et al 2021 ; Gurney et al 2021 ; Jacob et al 2021 ; Kuzuu et al 2021 ; Patt et al 2020 ; Peacock et al 2021 ; Piontek et al 2021 ; Reichardt et al 2021 ; Ruiz-Medina et al 2021 ; Stang et al 2020 ; Tsibulak et al 2020 ; Vardhanabhuti and Ng 2021 ; Voigtländer et al 2021 ). For example, a study, using national data from New Zealand, showed that cancer registrations (new diagnoses of primary malignant cancers) declined by 40% in this country in March–April 2020 compared with 2018–2019, and that registrations increased in the subsequent months to reach pre-lockdown levels (Gurney et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, as consequence, the virus was dubbed a novel coronavirus in 2019. A coronavirus seems to be a single-stranded, encapsulated ribonucleic acid with surface spikes that are 9 to 12 nm long and mimics the solar corona [ 43 , 44 , 45 ]. The spike (S) protein interacts with the angiotensin-converting enzyme 2 (ACE2) receptor and facilitates viral entrance into the host cell by mediating fusion of the enveloped and host cell membranes, and the coronavirus genome encodes four key structural protein molecules on the surface [ 46 , 47 ].…”
Section: Etiologymentioning
confidence: 99%
“…At the beginning of the pandemic, most countries around the world underwent a strict lockdown that had serious social, economic and health service effects. As a consequence, many non-COVID-19 diseases, such as tuberculosis [3] and cancer [4], suffered delays in diagnosis and treatment, leading to more severe illness and outcomes.…”
Section: Introductionmentioning
confidence: 99%